Sustainable layout design of steel buildings through embodied energy and costs optimization - Ahmed M. Elsayed (Elsevier, 2021)
Structural design process is a major phase in construction that has an impact not only on the cost of the project but on the environmental aspects as well. Although the majority of structural engineers aims to reduce the structural cost by reducing the weight of the elements, yet a handful of engineers has the information required to consider the environmental impact of their decisions. This paper presents an attempt to develop a multi-objective optimization model for steel floor structural system against cost and embodied energy using genetic algorithm. In addition, a novel study is conducted to address the embodied energy values for structural materials is Egypt. The presented model allows for determining the optimum layout of certain space taking into consideration the architectural constraints imposed on this space. In this optimization problem, the layout configuration of the steel beams, the steel beams profiles, the metal deck thickness, and the concrete slab thickness are determined. The developed model is elaborated along with the results of applying the model on two problems, which shows its ability to address several types of applications.